2003
DOI: 10.1002/anie.200390186
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range Electronic Coupling in Various Oxidation States of a C4‐Linked Tris(β‐diketonato)ruthenium Dimer

Abstract: Despite an increasingly varied experimental data basis [1] and sophisticated theoretical approaches [2] there is still only a rudimentary understanding of which factors govern the extent of interaction between metal centers in formally symmetrical mixed-valent compounds. Such compounds can be considered as intermediates in ™degenerate∫ inner-sphere metal-to-metal electron transfer. The interplay between metal configurations, the metal±ligand interface, and the properties of the ligand bridge has to be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Hoshino et al have shown that the introduction of alkyne group at the c-position of a b-diketonato chelate ring can lead to several oligomers or polymers with interesting properties [1,[4][5][6]. Nevertheless the way they prepare their building blocks is long and tedious [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hoshino et al have shown that the introduction of alkyne group at the c-position of a b-diketonato chelate ring can lead to several oligomers or polymers with interesting properties [1,[4][5][6]. Nevertheless the way they prepare their building blocks is long and tedious [4].…”
mentioning
confidence: 99%
“…A terminal alkyne can form a bridging group between two metal atoms or organometallic moieties [1][2][3]. Hoshino et al have shown that the introduction of alkyne group at the c-position of a b-diketonato chelate ring can lead to several oligomers or polymers with interesting properties [1,[4][5][6].…”
mentioning
confidence: 99%
“…The 1 H, 13 C, 31 P and 195 Pt NMR spectra were recorded on a Bruker Avance DRX 500 MHz spectrometer in CDCl 3 as solvent. The operating frequencies and references, respectively, are shown in parentheses as follows: 1 H (500 MHz, TMS), 13 C (125 MHz, TMS), 31 P (202 MHz, 85% H 3 PO 4 ), and 195 Pt (107 MHz, aqueous Na 2 PtCl 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The NMR spectra of complex 3. (A): 1 H in the Me region; (B): 31 P NMR and (C) 13 C NMR in the Me region. The peak labeled * in 1 H NMR is due to water of CDCl 3 solvent.…”
Section: Synthesis and Characterization Of The Pt(ii)ept(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation